Pengelolaan Perpustakaan Nagari di Situjuah Banda Dalam Kecamatan Limo Nagari Kabupaten 50 Kota - Agusni, Mezilia; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
In this paper is described about. Library management Situjuah Nagari Nagari Banda In Limo District. This research aims to describe: (1) How to manage Situjuah Banda In Nagari Library District? (2) what are the constraints faced in the management of the library in the district of Banda Situjuah Nagari Nagari Limo? Data were collected through observation and interviews in the Library Situjuh Nagari Nagari Banda In Limo District. Data analysis was performed descriptively. Conclusions are found of writing are as follows: (1) State Library Nagari Situjuah In Banda is not optimal, and the building is not owned by the library are less strategic location have not been able to accommodate hundreds of people, who are members of the public library is Situjuh Banda In. Besides, it has a library of structures and facilities are not adequate. (2) Collections Library Nagari Situjuah Banda has not cater to individual needs in the user library that consists of the main text books, supporting textbooks, reference books, fiction and non-fiction books as well as periodicals, newspapers and tape. However there are a few collections that need to be added. (3) In the processing of library collections in Nagari Situjuah Banda has not been performing all processing activities. (4) In the processing of library collections in Nagari Situjuah Banda has not been performing all processing activities. (5) The library staff strive to develop a collection of libraries and collections processing to perform well. Keywords: library management; library collections